دراسة تأثير بعض الركائز في إشارة الامتصاص الذري لعنصر الرصاص (Latakia University Journal -Basic Sciences Series, 2018)
تضمنت هذه الدراسة تأثير بعض الأوساط (HNO3, HCl, H2SO4, NaCl, NaF) في إشارة الامتصاص الذري لعنصر الرصاص ( تأثير هذه الأوساط في المنحنيات الحرارية للرصاص، ودراسة تأثير سلسلة من التراكيز لهذه الأوساط في إشارة الامتصاص الذري). استخدمنا الأنبوب المطلي والأنبوب ذا الصفيحة مع مصحح الديتريوم، كما استخدمنا كلا الأنبوبين مع مصحح الـ SR عند دراسة تأثير وسطي NaCl, NaF في إشارة الامتصاص الذري لنزر عنصر الرصاص. تبين وجود تأثير واضح للركازة على سرعة تطاير وتذرير عنصر الرصاص، كما لحظ ارتباط إشارة الامتصاصية اللانوعية بنوع الركازة المرافقة، وأظهر الأنبوب ذو الصفيحة قدرة على فصل قمم الامتصاصية النوعية عن قمم الامتصاصية اللانوعية مما يعكس قدرته الجيدة على تخفيض إشارة الامتصاصية اللانوعية، وعلى التخلص من تداخلات الركازة، والضجيج. لم يقدم مصحح الـSR أية فائدة إضافية عن مصحح الديتريوم، كما أن حساسية التحليل باستخدام مصحح الـSR أقل ( حوالي 50% ) من حساسية التحليل باستخدام مصحح الديتريوم. This study included the effect of some matrixes (HNO3, HCl, H2SO4, NaCl, NaF) on the atomic absorption signal of lead element by studying the effect of these matrixes on the thermal programs of lead. It also studied the effect of series concentrations of these matrixes on the atomic absorption signal, using both coated tube and platform tube with deuterium corrector, in addition to self-reversal corrector for NaCl and NaF only. There are clear effects according to the used matrix on the evaporation and atomization rate of lead, and a correlation between nonspecific absorption signal and the kind of matrix. The platform tube shows an ability to separate between the peaks of specific absorption and nonspecific absorption for both NaCl and NaF, which reflect its ability to reduce the nonspecific absorption signal, in addition to matrixes interferences and the noise. The SR corrector has no further use than the deuterium corrector. In addition, the analytical sensitivity of SR corrector is lower (about 50%) than the analytical sensitivity of deuterium corrector.